Thank a farmer - Gianferrari, Maria (Norton Young Readers, 2023)
Bread, milk, wool, fruits, and vegetables: things that fill our day to day lives. But where, and who, do they come from? Across wheat fields and city rooftop gardens, mushroom beds and maple forests, Thank a Farmer traces the food and clothing that a family uses back to the people who harvested and created them. With Maria Gianferrari's informed and poetic text and monumental artwork from Monica Mikai, Thank a farmer gently emphasizes the importance of agriculture in our day-to-day lives and reminds readers to give thanks to farmworkers around the world.